A psychiatric medication, clozapine, induces autophagy and apoptosis in breast cancer cells through reactive oxygen species - Ya-Chun Fan; Shih-Chao Lin; Po-Jung Lai; Pei-Chun Lai; Germain Maurus; Shiow-Yi Chen (PLoS ONE, 2025)
Cancer patients with psychotic disorders have occasionally exhibited reduced tumor sizes following long-term antipsychotic treatment. Previous studies have shown that antipsychotic drugs, such as clozapine, could inhibit cancer cell proliferation, but the underlying mechanisms remain unclear. This study investigates the anti-tumor effects of clozapine on breast cancer cells and explores its mechanisms of action. We used clonogenic and MTT assays to assess cell proliferation, flow cytometry and western blotting analyses to evaluate cell cycle distribution, apoptosis, and autophagy following clozapine exposure. The results show that clozapine downregulates Cyclin D1, CDK4, and CDK6, while upregulating p21 and p27 in MCF-7 cells, leading to G0/G1 phase arrest. Clozapine exposure also increases reactive oxygen species (ROS), apoptosis and autophagy levels. Notably, treatment with the antioxidant α-Tocopherol restores cell viability and reduces ROS and autophagy, indicating that ROS plays a central role in clozapine-induced cytotoxicity. Additionally, inhibition of autophagy using chloroquine enhances clozapine-induced apoptosis and further reduces cell viability. These findings suggest that clozapine induces apoptosis and autophagy through ROS generation and that combining clozapine with autophagy inhibitors could sensitize MCF-7 cells to treatment. Furthermore, clozapine induces significant cytotoxicity in MDA-MB-231 cells, an aggressive, ER-negative breast cancer model, through similar ROS- and autophagy-mediated mechanisms. The addition of α-Tocopherol similarly rescued these cells from clozapine-induced cell death. Overall, our study demonstrates that clozapine suppresses the growth of both MCF-7 and MDA-MB-231 breast cancer cells by inducing cytotoxicity via ROS and autophagy, highlighting its potential as a therapeutic agent, especially in combination with autophagy inhibitors.